Thermal performance of four-lobe swirl generator and its transition parts under a different type of nanofluids - Diabis, Farag. A; Abu Talib, Abd Rahim; Al-Tarazi, Yazan; Mazlan, Norkhairunnisa; Supeni, Eris Elianddy (Semarak Ilmu Publishing, 2022)
Due to the importance of promoting the thermal performance of heat exchangers, innovating a new technique is the main goal of many researchers. In swirl flow techniques, keeping the pressure drop at the practical level still requires more and more attention. In the current paper, a numerical study is conducted to explore the impact of a novel lobe swirl generator and its transition parts on forced convective heat transfer and friction factor in a circular pipe subjected to constant heat flux.The swirl mechanism is investigated at the pitch to a diameter of P/D = 8 as the optimum design. The transition part under several parameters of variable beta (β), transition multiplier (n= 0.5) and variable helix (t = 1) have been adopted. The effect of SiO2, Al2O3, and CuO volume concentrations (1 to 5%) in water under various Reynolds numbers (Re) from 15,000 to 35,000 have been carried out. The turbulent swirling flow was modelled using the applicable shear-stress transport (SST) k-ω. The outcome demonstrated an enhancement in heat transfer value ranging from 1.35 to 1.87 with an increased pressure drop value from 1.23 to 1.67. It was also found that using SiO2/water at 5% volume concentration and Re 15000 created the highest thermal performance, with a significant factor of 1.67.